Glass-fiber reinforced composite in management of avulsed central incisor: a case report - (:unkn) unknown (My University, 2004)
Reimplantation failure of avulsed anterior tooth in an adolescent patient requires removal of the failed tooth and consideration of restorative options. These options may include a removable partial denture, conventional 3-unit fixed partial denture, implant, or a resin-bonded appliance with a metal substructure (Maryland bridge). The glass-fiber reinforced composite material (everSTICK, StickTech Ltd, Turku, Finland) offers a restorative solution that is conservative and esthetic when compared to other restorations. Advantages include reduction of cost compared to conventional bridges, saving of time, elimination of second visit, ease of application, absence of metal allergy, ease of cleaning, and naturalness of feel. Its limitations include occlusal factors, and the presence of unsuitable abutment teeth. Another traditional contraindication is the presence of diastemas, which may limit the potential esthetic gains. This case of an 11-year-old girl, addresses the indications, preparation guidelines, and restorative procedures for an everSTICK bridge.
Keywords: Female; Humans; Adolescent; Child; Maxilla; Incisor; Composite Resins; Tooth Avulsion; Denture Design; Denture, Partial, Fixed, Resin-Bonded; Glass; Space Maintenance, Orthodontic